Penggunaan Photogrammetry sebagai Media Periklanan untuk Mendukung Pariwisata dan Sebagai Pelestarian Digital dari Situs Lama "Gunung Wudel" di di Desa Potroyudan, Kecamatan Jepara, Kabupaten Jepara - Muhammad Fahd Diyar Husni; Husni, Muhammad Fahd Diyar; Nursanty, Eko (Perigel: Jurnal Penyuluhan Masyarakat Indonesia, 2025)
Tourism plays an important role in shaping the economic development of cities and communities. Heritage sites have a major impact on the economy, making an important contribution to economic growth and development. 3D digital conservation, apart from being useful for preserving historical heritage, also functions as promotional media by utilizing the Internet of Things (IoT). By making 3D models of historical heritage objects, apart from preserving cultural heritage sites, they are also used as promotional media to increase tourism and economic benefits for the community. From the results obtained, it can show satisfactory results. The 3D shape created can provide an overview and information about the geometric shape and condition of the heritage building site, which is quite well captured. The hope is that this can provide information and attract tourists to visit the historical site, namely "Mount Wudel" in Jepara. Making 3D models will of course increase their attractiveness and also serve as a medium for digital conservation.